Developing a safer road user behaviour index. (April 2021) - Jameel, Abeer Khudhur; Evdorides, Harry
Abstract: Road user behaviour is an essential factor of increasing the rate of traffic accidents worldwide. Road safety experts and scientists consider aspects of road users' behaviour to be the main risk factors for road fatalities. These factors include drinking alcohol, speeding, not wearing seat belts, not wearing helmets when riding two-wheeled vehicles, not using child restraints, consuming illegal drugs, and being distracted by mobile phone use. This paper aims to investigate the role of these factors in assessing the road user behaviour through aggregating them and build a composite indicator that can be used in countries benchmarking and cross countries comparison, then identifying most successful practises. To achieve this aim, data related to the selected indicators, life-saving rate, and real crash data were collected. The indicators were weighted using simple and theoretical methods. The weighted indicators were aggregated using simple additive method. The developed index was applied to 12 European countries to test the validation of the index through investigation the correlation between index' ranking of countries with the ranking according to the rate of fatalities. It is concluded that the developed composite indicator can be used to assess the role of using the protection system and speeding in the severity of the road crashes. However, the role of the remaining factors in the likelihood of crashes occurrence needs more investigation. It can be concluded also that the road users' behaviour is not the only factor of reducing the road fatalities in some countries. This enhances the multidimensional system approach of defining the road safety. Based on this, it is recommended to consider other factors in conducting research, developing indices of road safety, and in recommending solutions. The results show also that the UK, Sweden, Ireland and Ireland have the most successful strategies to improve the road user behaviour among the selected countries; therefore, it is recommended to take lessons from these practices. Highlights: An aggregated road user behaviour index is construced by aggregating indicators representing road user factors. The investigated factors are drunk-driver, speeding, protective system, consuming drugs, and using mobile-phone. The selected indicators are grouped into likelihood indicators and severity indicators The validation of the index is tested by comparing the index' ranking with the rate of fatalities' ranking. The indicators of speeding and using protecting systems are more valid to assess the crash severity.